A new way of looking at the Barnum effect and its links to personality traits in groups receiving different types of personality feedback - Poškus, Mykolas Simas (Psichologija, 2014)
The present study proposes a new way of looking at the Barnum effect. A theoretical model describing the relationship between personality traits, type of personality feedback, and acceptance of personality feedback is proposed and tested. The results of the study provide proof for the model, supporting the notion that personality feedback is accepted both rationally and irrationally, demonstrating that the Barnum effect is linked to personality traits and these links are moderated by the type of personality feedback that is provided. Based on the results of this study, it is recommended that overall ratings of the acceptance of personality descriptions as a measure of the Barnum effect should be avoided. Rather, researchers should gather the acceptance ratings of the whole personality description presented as feedback, as well as acceptance ratings of its component statements. Any correlations between the acceptance ratings of the whole personality description and other variables should be controlled for the acceptance ratings of the component statements of the whole personality description.